PENGARUH TOTAL ASET DAN BAGI HASIL PERBANKAN TERHADAP VOLUME DANA PIHAK KETIGA (DPK) PADA BANK UMUM SYARIAH - Riauwanto, Selamat; Sulastiningsih, Sulastiningsih (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2019)
This study aims to analyze and determine the effects partially and simultaneously from internal banking factors in the form of: Total Assets and Banking profit sharing for Third Party Funds at Banks Sharia General. This research method used multiple linear regression analysis with the help of Eviews 8 software which is used to test the effect of independent variables in the form of Total Assets and Profit Sharing on the volume of Third Party Funds (DPK) in Islamic Commercial Banks. The sample of this study was 10 Islamic Commercial Banks, so that there were 50 annual reports obtained through purposive sampling, then analyzed using multiple linear regression methods. The results showed that based on F Test, the independent variable had an effect on DPK, indicated by the F value of 46.08032 and the significance of 0.000000 as a whole the independent variable was able to explain the effect of 82.14%. While based on the partial t test, it showed that Total Assets have a significant positive effect with a significance value below 0.05 (5%). Meanwhile profit sharing does not affect Third Party Fund Volume.